The efficiency of information system designed for servicing the adaptive computer-based system of production control - Baltovskyi, O. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper contains general requirements, basic conditions of technical support, problems of methodology and algorithms of determination system of information servicing efficiency integrated in automated system of production control.